2014
DOI: 10.4037/ajcc2014954
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of an Electromagnetic Feeding Tube Placement Device in Detecting Inadvertent Respiratory Placement

Abstract: Background Use of technology capable of electromagnetically tracking advancement of a feeding tube on a monitoring screen during insertion may enable detection of deviation of the tube from the midline as it advances through the chest, possibly indicating entry of the tube into the right or left main bronchus. Purposes To describe (1) published peer-reviewed studies that report on the detection of malpositioned tubes inserted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 15 publications
2
20
0
Order By: Relevance
“…11,12 Electromagnetic placement devices have been suggested as a replacement for radiographic confirmation of feeding tube placement at the bedside, although adverse outcomes have been reported, implying that a high level of user expertise may be necessary to obtain consistently positive results. 25 The 2 verification methods used most often by critical care nurses for initial verification of feeding tube placement in our study were observation for signs of respiratory distress and visual observation of aspirate from the feeding tube. These 2 methods are less reliable than capnography and pH methods.…”
Section: Discussionmentioning
confidence: 99%
“…11,12 Electromagnetic placement devices have been suggested as a replacement for radiographic confirmation of feeding tube placement at the bedside, although adverse outcomes have been reported, implying that a high level of user expertise may be necessary to obtain consistently positive results. 25 The 2 verification methods used most often by critical care nurses for initial verification of feeding tube placement in our study were observation for signs of respiratory distress and visual observation of aspirate from the feeding tube. These 2 methods are less reliable than capnography and pH methods.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of adverse events reported in the MAUDE database suggested that users were unable to identify feeding tube placement outside of the gastrointestinal tract. As described by Metheny and Meert, 12 skill of the clinician is an important variable to consider for CORTRAK-assisted insertions of feeding tubes. It is important to point out, however, that errors in confirmation of feeding tube placement have also been made by misinterpretation of radiographs, 12,18 often when interpretation was performed by someone other than a trained radiologist.…”
Section: Discussionmentioning
confidence: 99%
“…10,11 Despite this advantage, in a recent review of studies of electromagnetic placement devices, researchers expressed concern that a higher level of user expertise may be required for safe use of this device. 12 Because other verification methods for blindly inserted feeding tubes, such as pH measurement, capnography, visualization of gastric aspirate, and assessment for respiratory distress lack validity, it is imperative to establish an accurate and reliable method for verifying feeding tube insertion at the bedside. Auscultation (air bolus) and water bubbling methods should no longer be used for verification of feeding tube placement because those methods are inaccurate.…”
mentioning
confidence: 99%
“…Multiple cases have been reported in which clinicians failed to recognize placement of feeding tubes in the respiratory tract while using an ETP device; some of these were associated with fatal outcomes. 53,54 Reports of clinicians failing to recognize tube perforations through the nasopharynx or esophagus while using an ETP device have also been published. 55,56 Radiographic Confirmation 1.…”
Section: Aacn Practice Alertmentioning
confidence: 99%
“…A properly obtained and interpreted radiograph is recommended to confirm correct placement of any blindly inserted tube (small bore or large bore) before its initial use for feedings or medication administration 1,11,[57][58][59][60][61][62][63] ; the same recommendation applies to a tube inserted with assistance from ETP device. 52,53 Because radiographs may be misinterpreted, 39,45,58,64 it is best to have a radiologist interpret the film to approve use of the tube for feedings. 1 2.…”
Section: Aacn Practice Alertmentioning
confidence: 99%